Determinants of job satisfaction and performance of seafarers - Yuen, Kum Fai (2019)
The ability to motivate and retain seafarers is a critical manpower issue in view of global labour shortage and high turnover rate among seafarers. The objective of this paper is to analyse the core determinants of job satisfaction and performance of seafarers. A survey was administered on 116 seafaring officers and the obtained data were analysed using structural equation modelling. The results show that job satisfaction is considerably correlated with job performance of seafarers. In addition, the amount of stress associated with working onboard a ship and attractiveness of rewards are key determinants of job satisfaction. The dispositions of seafarers and appeal of the job design also have considerable impacts on job satisfaction. Based on literature review and post-survey interviews, a management model consisting of policies and strategies to motivate and retain seafarers is proposed.